Response of Acacia nilotica to Silvicultural Practices in Waterlogged Sodic Soil - Singh, S. B.; Bhatnagar, Sanjeev (Indian Forester, 2003)
A field experiment was conducted on waterlogged sodic soil to see the response on Acacia nilotica to silvicultural practices. The experiment consisting of 8 treatments (control, weeding, lopping, fertilizer application and their possible combinations) was laid-out in Randomized Block Design, replicated twice. Plant height recorded at six months interval and biomass after two and half years of treatment revealed that lopping increased the plant height but it was not beneficial to increase the biomass. Fertilizer application was found to increase plant height, circumference and biomass production of the plants. Response of weeding treatment was not promising.